Evaluating the importance of accurate sex ratios on egg deposition targets and conservation limit compliance for Atlantic salmon (Salmo salar L.) in the River Tamar, south‐west England. (30th November 2022) - King, R. Andrew; Toms, Simon; Stevens, Jamie R.
Abstract: Effective management of Atlantic salmon requires a suite of metrics that are fed into stock assessment models to assess stock compliance within individual rivers in relation to estimated conservation limits. Key among metrics required to assess compliance are the number of adult female spawners within each adult sea age class and their corresponding egg deposition rates. Owing to the current need to conserve salmon stocks, adult sex ratios used to calculate egg deposition estimates often depend on data derived from historic lethal sampling. Using non‐invasive sampling and an accurate genetic sex test, we determined the proportion of female fish in two adult life history stages (one sea winter and two sea winter) of Atlantic salmon from the River Tamar, an Environment Agency (England) Monitored River. Our results suggested that phenotypic‐based sexing of Tamar salmon was unreliable, especially for early run fish and that the proportion of female salmon has been under‐estimated, thereby leading to consistent under‐estimation of egg deposition rates.